PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN DARING - Zahwa Ayunda Salsabilla; Bayhakki Bayhakki; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Since the entry of the Corona virus outbreak in Indonesia, Kemendikbud has instructed to implement distance learning (online). Learning through online is done without face to face, but through the internet and networks and every student has a different perception of the implementation of this online learning This study aims to determine student perceptions of online learning at Riau University Nursing students This study used a descriptive correlational design with a cross-sectional approach. The research sample was 242 respondents using a simple random sampling technique. The analysis used univariate analysis to see the frequency distribution. The measuring instrument used is an online learning perception questionnaire consisting of 12 statements that have been tested for validity with r count 0.461-0.745 > r table (0.444). The questionnaires were distributed via a google form. The results showed that the majority of students had a positive perception of online learning (51.7%). Students are expected to be more active and enthusiastic in participating in online lectures and increase understanding related to online learning so that they can operate and follow the online learning process comfortably.Keywords:University Student, Online Learning, Perception.